Study on signal of frequency modulated continuous wave ranging - Li Guang (Dianzi Jishu Yingyong)
That the frequency of frequency modulated continuous wave(FMCW) signal varies periodically makes the traditional time-frequency analysis very difficult and crabbed. The phase of the beat signal is analyzed in this paper. The beat signal is proved to be periodical and its spectrum is discrete. The power is distributed to all the harmonics. The weight of each harmonic depends on frequency deviation,distance,modulation period. When the target moves in radial direction, spectrum of beat signal is influenced by Doppler effect and becomes nonperiodic when the Doppler shift is not an integral multiple of original repetition frequency.